5 - La recherche à la Faculté des lettres et sciences humaines de l’Université Cheikh Anta Diop de Dakar : bilan de 50 ans d’activités - Moustapha Tamba, (Journal of Higher Education in Africa, 2009)
This article is about the results of 50 years research (1957-2007) at the Faculty of Arts and Humanities. The survey focused on documents provided by the Vice-Chancellery, the Faculty, the Departments. The information has been collected from the Faculty of Arts and Humanities’ Review, from the M.A Dissertations of the different departments and from the catalogue. The article highlights the increasing pace of scientific production during the last decade and the important place occupied by master’s thesis in this growth.